Coordinated Singing in Coppery Titi Monkeys (Plecturocebus cupreus): Resource or Mate Defense? - Dolotovskaya, Sofya; Heymann, Eckhard W. (Frontiers in Ecology and Evolution, 2022)
Coordinated singing, performed as duets by mated pairs and often joined by offspring to form choruses, is a distinctive behavioral attribute of the social system of pair-living and pair-bonded Neotropical titi monkeys. Duets and choruses are presumed to be associated with mate or territorial defense, but no consensus has yet been reached regarding their function. Here, we examined temporal and spatial patterns of coordinated singing in eight wild groups of coppery titi monkeys, Plecturocebus cupreus, in Peruvian Amazonia to test predictions of the joint resource and mate defense. We investigated singing rates in relation to female reproductive state, fruit consumption and demographic context using a dataset based on 227 observation days and analyzed temporal and spatial distribution of songs using a dataset based on 150 songs, collected between June 2017 and September 2021. Titi monkeys sang least frequently when females were likely to be sexually receptive and most frequently when females were likely to be pregnant. Groups also sang slightly more often when fruits were consumed more intensively, although this association did not reach statistical significance. The duration of songs was not associated with female reproductive state or fruit consumption, but songs were longer during inter-group encounters compared to non-encounter contexts. Songs were not concentrated in the core areas of home ranges; rather, they were distributed throughout the home ranges in concordance with its use. Finally, songs were concentrated around dawn. Our results provide support for a function in joint resource defense and inter-group communication of coordinated songs in coppery titi monkeys. The function of coordinated songs for mate defense in the form of paternity guarding, on the other hand, was not supported by our findings.